Shorter Total Length of Stay After Intraperitoneal Fosfomycin, Metronidazole, and Molgramostim for Complicated Appendicitis: A Pivotal Quasi-Randomized Controlled Trial - Fonnes, Siv; Roepstorff, Søren; Holzknecht, Barbara Juliane; Olesen, Christoffer Skov; Olsen, Joachim Hjalde Halmsted; Schmidt, Line; Alder, Rasmus; Gamborg, Sara; Rasmussen, Tilde; Arpi, Magnus; Jørgensen, Lars Nannestad; Rosenberg, Jacob (Frontiers in Surgery, 2020)
Background We aimed to investigate the difference in the total length of hospital stay (LOS) after intraperitoneal versus intravenous antibiotic treatment in patients with complicated appendicitis. Methods We conducted a quasi-randomised prospective clinical trial. The intervention group received 4 g fosfomycin, 1 g metronidazole, and 50 µg recombinant human granulocyte-macrophage colony-stimulating factor intraperitoneally, which was left in the abdominal cavity, immediately after laparoscopic appendectomy. Postoperatively, this group received antibiotics orally. The control group received intravenous antibiotics both during surgery and postoperatively. We primarily evaluated total LOS within 30 days. Furthermore, we evaluated harms and adverse events, Gastrointestinal Quality of Life Index, postoperative complications, and convalescence. Participants were followed for 30 days postoperatively. Results A total of 12 participants concluded the trial. The total LOS was significantly shorter in the intervention group (six participants, median 13 hours; range 2-21 hours) than in the control group (six participants, median 84 hours; range 67-169 hours), p=0.017. Comparable harms and Gastrointestinal Quality of Life Index scores were found in the two groups. The time to return to normal activities was median six days and 10 days for the intervention and the control group, respectively. There were no serious adverse events related to the trial nor any complications in the intervention group. In the control group, two patients developed intraabdominal abscesses. Conclusions The intervention group had a significantly shorter total LOS. The study was not powered to assess differences in complications, but the results indicate that the intervention seems to be a safe regimen, which can be investigated further to treat patients with complicated appendicitis.